2019
DOI: 10.1080/2162402x.2019.1571388
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of infiltrating B cells and their clinical significance in human hepatocellular carcinoma

Abstract: As a major cellular component in tumor microenvironment, the distribution, frequency, and prognostic significance of infiltrating B cell subsets in hepatocellular carcinoma (HCC) remain controversial. Using tyramide signal amplification (TSA) based fluorescent multiplexed immunohistochemistry in situ, we evaluated the distribution and frequency of B cell subsets in two independent HCC cohorts (n = 619). The results were further confirmed by flow cytometry. Correlations of B cell subsets with clinicopathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
100
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 44 publications
(48 reference statements)
10
100
1
Order By: Relevance
“…Naive B cells represent one of the differentiation stages of B cells, which is one of the mechanisms of autoimmune tolerance. Similar to our results, Zhang et al also found that naive B cells were associated with superior survival of LIHC patients. Eosinophils are components of the immune microenvironment that modulate tumor initiation and progression, playing an antitumorigenic role in gastric, colorectal, and many other cancers .…”
Section: Discussionsupporting
confidence: 92%
“…Naive B cells represent one of the differentiation stages of B cells, which is one of the mechanisms of autoimmune tolerance. Similar to our results, Zhang et al also found that naive B cells were associated with superior survival of LIHC patients. Eosinophils are components of the immune microenvironment that modulate tumor initiation and progression, playing an antitumorigenic role in gastric, colorectal, and many other cancers .…”
Section: Discussionsupporting
confidence: 92%
“…The immune microenvironment of HCC is a mixture of heterogeneous immune components (7,8), immune cells migrate from the hematopoietic organ to the liver, establish an active immune niche that interacts with stromal cells, and affect differentiation, tumorigenesis and development. Therefore, it is important to explore the composition and state of immune cells during tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the majority of patients worldwide with HCC have underlying cirrhosis (12). On a global basis, some common risk factors lead to inflammatory fibrosis or cirrhosis, accompanied by extensive immune infiltration, which is considered to be a key factor in the development and progression of HCC (7).…”
Section: Introductionmentioning
confidence: 99%
“…They respond to reencountered antigens by forming germinal centers (GC) and rapidly producing antibodies [47]. It is reported that high density of tumor-in ltrating memory B cells is closely related to superior survival [48][49][50]. In our study, the density of memory B cells in TME of female patients with LUAD was signi cantly higher than that in TME of male patients (Fig.…”
Section: Discussionmentioning
confidence: 53%